Pengaruh Gaya Hidup Terhadap Keputusan Pembelian Dan Kepuasan Konsumen Sepeda Motor Kawasaki D-Tracker 150 Di Kota Dumai - Fajri Mubarak Natsir; Zulkarnain; Alvi Furwanti Alwie (Ikatan Sarjana Ekonomi Indonesia Cabang Pekanbaru, 2020)
This study aims to see and know the direct and indirect effects of lifestyle on purchasing decisions and consumer satisfaction. The population in this study were 500 respondents from Dumai City who bought and used a Kawasaki D-Tracker 150 motorcycle, using Path Analysis. In this study the sampling method uses the Probability Sampling Technique, which is a sampling technique that provides equal opportunities for elements of the population to be selected as sample members. In this study the authors set a sample of the criteria of respondents, namely age 17 years and above. Samples taken in this study used the Slovin formula. The results in this study that lifestyle has a positive and significant effect on consumer purchasing decisions. Lifestyle and purchasing decisions have a positive and significant effect on customer satisfaction. There is an indirect effect of Lifestyle on Consumer Satisfaction through Decisions